Design and Implementation of Automatic Detection System of Gear Grinding Burn - Lin Jiachun; Huang Shaoyu (Jixie chuandong)
For the detection of grinding burn about tooth flank of cylindrical gear and bevel gear after grinding,the grinding burn detection system based on manipulator is proposed,which improves the degree of automation and reliability.The Barkhausen noise inspection method for detection grinding burn is focused on introduced.The automatically detected is performed by the sensor on a robot and a turntable.The experimental results demonstrate the feasibility of this method for quality control in gear production.